2017
DOI: 10.1016/j.gdata.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequence of Bacillus oleronius DSM 9356 isolated from the termite Reticulitermes santonensis

Abstract: Bacillus oleronius strain DSM 9356 isolated from the termite Reticulitermes santonensis was sequenced to gain insights in relation to its closest phylogenetic neighbor Bacillus sporothermodurans. The draft genome of strain DSM 9356 contains 5,083,966 bp with an estimated G + C content of 35%, 4899 protein-coding genes, 116 tRNAs and 18 rRNAs. The RAST annotation assigned these genes into 462 subsystems, with the maximum number of genes associated with amino acids and derivatives metabolism (14.84%), followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Bacillus sporothermodurans strains SAD, SA01, BR12, and DSM 10599, as well as B. oleronius DSM 9356, were sequenced and annotated as previously described [15,16]. Subsequent analyses in this study are based on the strains mentioned above.…”
Section: Genome Sequencing and Analysismentioning
confidence: 99%
“…Bacillus sporothermodurans strains SAD, SA01, BR12, and DSM 10599, as well as B. oleronius DSM 9356, were sequenced and annotated as previously described [15,16]. Subsequent analyses in this study are based on the strains mentioned above.…”
Section: Genome Sequencing and Analysismentioning
confidence: 99%
“…Previous work reported difficulties in assembling Heyndrickxia species genomes using a short-read sequencing approach [ 13 , 18 , 20 ]. Therefore, we utilized hybrid assembly of Illumina short-read and MinION long-read sequences of type strain H. sporothermodurans DSM 10599 T , which mostly yielded a single coherent chromosome sequence instead of a few hundred contigs.…”
Section: Discussionmentioning
confidence: 99%
“…Heyndrickxia oleronia is phylogenetically closely related to H. sporothermodurans and was found to be difficult to distinguish from the latter on the basis of biochemical and physiological characteristics solely [ 4 ]. The draft genome of H. oleronia was published 2017 by Owuso-Darko et al [ 20 ] with more than 500 contigs after sequence assembly. This underlines the difficulty of assembling Heyndrickxia species genomes using a sequencing technique such as Illumina MiSeq sequencing that generates short-reads only.…”
Section: Introductionmentioning
confidence: 99%
“…The 16S rRNA gene of Microaerobacter geothermalis Nad S1 T shared 90 to 92% sequence identity with those of other species affiliated with the family Bacillaceae ( 1 ). The genome comparison analyses indicated that the Nad S1 T genome shared 65.4 to 66.8% ANI with other type species genomes, such as those of Tepidibacillus fermentans , Vulcanibacillus modesticaldus , Melghiribacillus thermohalophilus , and Heyndrickxia oleronia ( 10 13 ). In addition, none of the curated genomes listed in the GTDB ( 9 ) was closely related to the Nad S1 T genome.…”
Section: Announcementmentioning
confidence: 99%